2018
DOI: 10.1080/09540121.2018.1445826
|View full text |Cite
|
Sign up to set email alerts
|

“It is not possible to go inside and have a discussion”: how fear of stigma affects delivery of community-based support for children’s HIV care

Abstract: Caregivers mediate children’s access to HIV care and their adherence to treatment. Support for caregivers may improve health outcomes in children, but fear of HIV stigma and discrimination can affect both uptake and delivery of support services. Within a trial evaluating community-based support for caregivers of newly HIV diagnosed children in Harare, Zimbabwe, we conducted a longitudinal qualitative study to explore how stigma affected delivery and acceptance of the intervention. We conducted semi-structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
(42 reference statements)
1
11
0
Order By: Relevance
“…In addition to text messaging challenges, community adolescent treatment supporters were unable to visit some adolescents' homes-a recurring issue in community-based interventions. 35 Community adolescent treatment supporters were, however, able to meet study participants in neutral spaces, highlighting the value of differentiated service delivery in responding to beneficiaries' preferences. 14 Finally, although process evaluation data suggested the mechanisms of effect of the Zvandiri intervention, it is possible that unmeasured or unassessed variables might also have played a role in the intervention effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to text messaging challenges, community adolescent treatment supporters were unable to visit some adolescents' homes-a recurring issue in community-based interventions. 35 Community adolescent treatment supporters were, however, able to meet study participants in neutral spaces, highlighting the value of differentiated service delivery in responding to beneficiaries' preferences. 14 Finally, although process evaluation data suggested the mechanisms of effect of the Zvandiri intervention, it is possible that unmeasured or unassessed variables might also have played a role in the intervention effect.…”
Section: Discussionmentioning
confidence: 99%
“…To support the implementation of the intervention at scale, continuing to budget for intensive mentor support for new cohorts of CATS and investing in it as an integral principle of youth peer support is vital [26]. This would ensure that there is adequate support to ameliorate the cluster of challenges relating to stakeholder resistance, concerns around the occupational risks of deductive disclosure and related stigma [30,31] and under-appreciating the value of peer-supporters, which can occur upon initial roll out of the intervention within communities. The findings demonstrate the supportive value that the CATS gain from each other, in common with various manifestations of peer support [32], but also illustrate that this can be further reinforced by the opportunities to mentor and be mentored through the provision of ongoing training and coordination meetings with peers [17].…”
Section: Discussionmentioning
confidence: 99%
“…Our review search was conducted on 9 December 2016 and it is possible that some of the landscape regarding stigma and access to care may have changed in the ‘test and treat’ and differentiated service delivery era. However, after conducting an updated search and rapidly appraising recently published studies (up till 1 August 2018), we identified several studies which supported our findings, specifically regarding quality of health services [130133], disrespectful health workers and the role of power in health service delivery [132, 134], lack of access to health services [130, 131], competing priorities and unpredictable life circumstances [135138], the role of the social world [131, 132, 139], influence of gender roles [140], medical pluralism [132, 141], the motivating influence of having dependents [142, 143], the challenges of same day ART initiation[144], the barriers to care caused by stigma [130, 131, 138, 143, 145, 146], challenges to accessing care for PWD [147], the benefits of support [131, 132, 148, 149], and fluctuations in engagement over time [131]. We therefore feel that the findings of this review remain relevant to current HIV populations.…”
Section: Discussionmentioning
confidence: 99%